Cost‐Effectiveness of Radiofrequency Renal Denervation in Taiwan Based on Clinical Evidence and Regional Event Rates - Hui‐Chun Huang; Khoa N. Cao; Anne M. Ryschon; Kee‐Wong Phay; Tzung‐Dau Wang; Jan B. Pietzsch (The Journal of Clinical Hypertension)
ABSTRACT Radiofrequency renal denervation (RF RDN) is recognized as an adjunct therapy for hypertension. This study evaluated the cost‐effectiveness of RF RDN for the Taiwanese healthcare system using results from the SPYRAL HTN‐ON MED randomized, sham‐controlled trial. A decision‐analytic Markov model projected clinical events, costs, and quality‐adjusted life‐years (QALYs) for RF RDN versus standard‐of‐care (SoC) in an Asian population context. Clinical event risk reductions from treatment effects on office‐based systolic blood pressure (oSBP) were derived from a meta‐regression study of 47 hypertension trials. SPYRAL HTN‐ON MED demographics and results (oSBP reduction of 4.9 mmHg against sham) were used in the base case analysis. The incremental cost‐effectiveness ratio (ICER) was assessed against a willingness‐to‐pay (WTP) threshold of three million Taiwan dollars (TWD) per QALY gained. Compared to SoC, RF RDN was projected to reduce clinical events, with relative risks of 0.80, 0.88, and 0.74 for stroke, myocardial infarction (MI), and heart failure (HF), respectively. The incremental costs and QALYs were 216 381 TWD and 0.25, respectively, resulting in an ICER of 850 932 TWD per QALY gained. The ICER was cost‐effective across a broad range of uncertainty analyses. Model‐based projections adjusted for East Asian event rates suggest RF RDN may significantly reduce events, making it a cost‐effective intervention in the Taiwanese healthcare system for treating uncontrolled hypertension.